FRAUDULENT FINANCIAL REPORTING: PENGUJIAN TEORI FRAUD PENTAGON PADA SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2017 - Venny, Lestari; Yuneita, Yuneita; Adhitya, Agri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This research aims to obtain empirical evidence about the efcetiveness of thefraud pentagon are External Pressure, ineffective monitoring, change in auditor, changein director and frequent number of CEO’s picture in detecting fraudulent financialreporting. The variables of the fraud pentagon that used is a pressure with proxyExternal Pressure (LEV), Opportunity with proxy ineffective monitoring (BDOUT),rationalization with proxy change in auditor (CPA), capability with proxy change indirector (dchange), and arrogance with proxy frequent number of CEO’spicture(CEOPIC). In this research uses a proxy earnings management with discretionaryaccruals as the dependent variable. The population of this research is the bankingcompanies listed in Indonesia stock exchange in 2014-2017. Total sample of this researchis 35 banking companies with four years observation, resulted in 140 firm-observation.Data analysis was performed with the classical assumption and hypotesis testing usingmultiple linear regression. The result indicates that the External Pressure (LEV),ineffective monitoring (BDOUT), change in auditor (CPA), change in director(DCHANGE), and frequent number of CEO’s picture(CEOPIC) influence the fraudulentfinancial reporting.Keywords : Fraudulent financial reporting, fraud Pentagon, external pressure,ineffective monitoring, change in auditor, change in director, frequentnumber of CEO’s picture